Problématiques associées au développement d’un bouchon d’oreille « intelligent » - Jérémie Voix; Frédéric Laville (Perspectives Interdisciplinaires sur le Travail et la Santé)
Many workers are exposed to noise levels high enough to put them at risk of losing their hearing. However, noise reduction at source, when technically feasible, is often difficult to implement for economic reasons. Therefore, individual protection remains the most widespread solution in practice.Unfortunately, the hearing protectors currently available on the market are seldom worn as continuously as they should be (because they are not very comfortable or must be removed to communicate) and are generally poorly adapted to the worker’s need for protection (because their actual attenuation is generally unknown).This article presents the issues found in the ongoing project on an earplug that would solve these problems. The issues are related to occupational health and safety aspects (non-continuous wearing of the hearing protector and unadapted protection), technical aspects (development of a comfortable earplug both from the physical and sound perception point of view and whose performances are measurable) and scientific aspects (modeling of physical systems, signal processing, instrumentation and measurement techniques).